Effects on Fatty Acid Compositions of Müsküle Grape Leaves (Vitis vinifera L.) of Different Harvest Times - Akin, Aydin; Baris Citil, Ozcan (Asian Journal of Chemistry, 2012)
The present study, deals with the fatty acid profile in six different harvest times of Müsküle grape leaves grown in Turkey. The fatty acid profile was determined using gas chromatography. Twenty eight fatty acids were detected in grape leaf oils. Generally, C 18:1 oleic acid, C 14:0 myristic acid, C 18:0 stearic acid, C 18:2 w6 linoleic acid, C 16:0 palmitic acid and C 18:3 w3 linolenic acid were found to be the major fatty acids in all dates. The monounsaturated fatty acids were determined at 37.43, 41.43, 45.18, 50.05, 51.75 and 54.96 % in 16.05.2010, 31.05.2010, 16.06.2010, 03.07.2010, 20.07.2010, 07.08.2010, respectively. Monounsaturated fatty acids content was found to be more than the polyunsaturated fatty acid content in all times. Despite of the saturated fatty acid showed a decrease against time; there was an increasement with the monounsaturated fatty acids.